A bulk-driven differential CMOS schmitt trigger with adjustable hysteresis for ultra-low-voltage operation. (August 2021) - Nejati, Ali; Radfar, Sara; Amiri, Parviz; Maghami, Mohammad Hossein
Abstract: In this paper, an ultra-low-voltage differential Schmitt trigger with two configurations of voltage-mode and current-mode is proposed. The designed Schmitt trigger utilizes the bulk-driven technique and is biased in the weak inversion region that makes it appropriate for operating with a small power supply of 0.4 ​V. The hysteresis characteristic of the proposed Schmitt trigger can be adjusted by the body bias technique, which is applied to the control transistors of the positive feedback without adding any other elements. Although the designed circuit is designed in the subthreshold region, it has a higher speed, and the variations of the hysteresis width are considerably wider compared to the similar works; i.e., the ratio of the hysteresis width to the voltage supply ( Δ W H V d d ) is up to 73.2%. Moreover, the power consumption of this circuit ranges between 85.2 and 120.4 ​nW, which is the minimum value compared to the recent CMOS Schmitt trigger circuit, and this makes it suitable for ultra-low-power applications such as biomedical devices.